2013
DOI: 10.2337/dc12-1694
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Crossover Study to Examine the Necessity of an Injection-to-Meal Interval in Patients With Type 2 Diabetes and Human Insulin

Abstract: OBJECTIVEPatients with diabetes and insulin therapy with human insulin were usually instructed to use an interval of 20–30 min between the injection and meal. We examined the necessity of the injection-to-meal interval (IMI) in patients with type 2 diabetes mellitus (T2DM) and flexible insulin therapy with human insulin.RESEARCH DESIGN AND METHODSIn this randomized, open crossover trial, 100 patients with T2DM (47% men, mean age = 66.7 years) were randomized to the IMI first group (phase 1, IMI 20 min; phase 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 17 publications
0
22
1
1
Order By: Relevance
“…Therefore for microneedles to become the preferred choice, insulin must be released as quickly as possible. Current data suggests that the optimal injection-to-meal (IMI) interval for both type 1 diabetics is between 20 and 30 min [32]. Therefore, based on this data, it is important for the polymer stabilizer to allow the insulin to be absorbed within this time frame.…”
Section: Release Studiesmentioning
confidence: 97%
See 1 more Smart Citation
“…Therefore for microneedles to become the preferred choice, insulin must be released as quickly as possible. Current data suggests that the optimal injection-to-meal (IMI) interval for both type 1 diabetics is between 20 and 30 min [32]. Therefore, based on this data, it is important for the polymer stabilizer to allow the insulin to be absorbed within this time frame.…”
Section: Release Studiesmentioning
confidence: 97%
“…However, emerging research has downplayed the importance of IMI in type 2 diabetics [32]. For a diabetic patient to achieve optimal blood glucose control, the amount of insulin injected must correlate with food intake after injection.…”
Section: Release Studiesmentioning
confidence: 99%
“…In addition to the ethical consideration, a washout period is often unnecessary for diabetes studies if the second period is long enough to allow the carryover effect of the first drug to disappear or diminish to an irrelevant level before measurement of the primary endpoint in the second period . Examples of clinical trials can be found in the literature . Antidiabetic medications, especially insulins, are not curative and usually do not have long half‐lives (<1 day) or duration of action.…”
Section: Carryover Effect and Washout Periodmentioning
confidence: 99%
“…For decades, the crossover design has been used for late‐phase clinical studies and widely used in pharmacokinetic (PK) and pharmacodynamic (PD) studies, as well as bioequivalence studies . Many medical device studies also used a crossover design to measure preference, usability, or safety endpoints, such as leakage, pain, wheal formation, etc .…”
Section: Introductionmentioning
confidence: 99%
“…However, a study of 100 patients with type 2 diabetes found no clinical benefit to using a 20-minute lag time compared with no lag time with mealtime regular insulin. 8 Based on this study, the lag time typically recommended with use of regular insulin may not be necessary, which would simplify the switch from rapid-acting insulin analogs at mealtime. Still, given the slow absorption of regular insulin, more data on this topic are needed.…”
Section: Thus Physicians Often Rely On Their Clinical Experiencementioning
confidence: 99%